2011
DOI: 10.1063/1.3645017
|View full text |Cite
|
Sign up to set email alerts
|

Spin-flop driven magneto-dielectric effect in Co4Nb2O9

Abstract: Co4Nb2O9 becomes antiferromagnetic (AFM) below 27.4 K with a spin-flop transition at a critical field, Hc, of 12 kOe. Room-temperature dielectric properties are dominated by finite electronic conductivity. Below 125 K, the charge carriers are frozen-out and the dielectric constant is controlled by the lattice phonons. A large (12%) spin flop-driven enhancement in dielectric constant is found in the very narrow temperature interval (Δ T = 1.6 K) in the vicinity of the AFM phase transition. Magneto-dielectric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
43
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 18 publications
15
43
2
1
Order By: Relevance
“…The unit cell consists of two formula units built up by three unit cells of the corundum type. The magnetic structure of Co 4 Nb 2 O 9 has been settled by Bertaut et al and recently confirmed by Schwarz et al282930 According to the result of neutron diffraction, two non-equivalent octahedral sites are occupied by Co I and Co II . The magnetic moments of the Co ions are parallel to c direction and form chains along the line (, , z ) (spin up) and (, , z ) (spin down), which is plotted in Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The unit cell consists of two formula units built up by three unit cells of the corundum type. The magnetic structure of Co 4 Nb 2 O 9 has been settled by Bertaut et al and recently confirmed by Schwarz et al282930 According to the result of neutron diffraction, two non-equivalent octahedral sites are occupied by Co I and Co II . The magnetic moments of the Co ions are parallel to c direction and form chains along the line (, , z ) (spin up) and (, , z ) (spin down), which is plotted in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The magnetic moments of the Co ions are parallel to c direction and form chains along the line (, , z ) (spin up) and (, , z ) (spin down), which is plotted in Fig. 1(b), resulting in a collinear antiferromagnetic spin structure with a magnetic point 30. This spin configuration is similar to that of Cr 2 O 3 , which breaks both the space-inversion and time-reversal symmetries and then allows a linear ME effect19.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the magnetodielectric effect exists in the entire temperature region below T N , not only near T N as reported previously. At the same time, the strain exhibits a drop below T N , and the magnetic field suppresses this anomaly, demonstrating magnetoelastic coupling in Co 4 Co 4 Nb 2 O 9 is a collinear antiferromagnet with a spin-flop transition at a critical field of about 12 kOe, and a dielectric peak around Néel temperature (T N ) under the magnetic field larger than this critical field is found by Kolodiazhnyi et al 1 Subsequently, magnetic field induced electric polarization and electric field control of magnetism is observed below T N by Fang et al 2 More recently, Khanh et al investigated magnetic structure and magnetoelectric response in single crystal sample, and the results suggest the in-plane antiferromagnetic order and the formation of a ferrotoroidic order in Co 4 Nb 2 O 9 . 3 However, none of them get much attention to the dielectric property below T N .…”
mentioning
confidence: 84%
“…The magnetic field has no effect on ε ′ in the high temperature region, but induce a sharp peak around T N in the ε ′ ∼T curve as reported previously. 1 The magnetic field also shifts up the plateaus of ε ′ in the low temperature region under zero magnetic field.…”
mentioning
confidence: 99%
“…According to previous report by Kolodiazhnyi et al . 6 , the structural space group of CNO is . And a magnetodielectric peak attributed to magnetically-driven spin-flop phase transition was observed in polycrystalline CNO near the antiferromagnetic phase transition temperature (T N  = 27.5 K) under a high external magnetic field (>12 kOe).…”
Section: Introductionmentioning
confidence: 99%